Pharmacokinetics and Genetic Factors of Atorvastatin in Healthy Korean Subjects - Kim, Serim; Seo, Jong Do; Yun, Yeo-Min; Kim, Hanah; Kim, Tae-Eun; Lee, Taeheon; Lee, Tae-Rim; Lee, Jun Hyung; Cho, Eun-Hae; Ki, Chang-Seok (Frontiers in Genetics, 2022)
Background: Statins are the most popular agents for the primary and secondary prevention of cardiovascular disease; however, the pharmacokinetic parameters and associated genetic factors in the Korean population have not been fully elucidated. This study explored the pharmacokinetic properties of atorvastatin and the association between genetic variations and atorvastatin pharmacokinetics in healthy Korean subjects. Methods: Atorvastatin (80 mg) was administered to 35 healthy Korean volunteers. Plasma levels of atorvastatin and its metabolites were measured sequentially using liquid chromatography-tandem mass spectrometry from 0 to 24 h after atorvastatin administration. Customized next-generation sequencing analysis was performed covering all coding exons of 15 genes, as well as 46 single-nucleotide variants in 29 genes related to statin pharmacokinetics. Results: The mean area under the concentration-time (AUC) and Cmax (maximum peak concentration) were 269.0 ng/mL∙h and 84.3 ng/mL, respectively, which were approximately two times higher than those reported in Caucasians. Genetic analysis revealed that 8 genetic variants in ABCB1, ABCG2, APOA5, CETP, and CYP7A1 contributed to the AUC of atorvastatin. The atorvastatin AUC0-24 h prediction model was developed based on age and 8 genetic variants using multivariate linear regression (adjusted R2=0.878, P < 0.0001). Conclusion: This study shows that the pharmacokinetic properties of atorvastatin in Koreans are different from those in Caucasians and that atorvastatin AUC0-24 h could be predicted based on age and 8 genetic variants of ABCB1, ABCG2, APOA5, CETP, and CYP7A1.